Genomic inbreeding estimation in small populations: evaluation of runs of homozygosity in three local dairy cattle breeds. (6th January 2016) - Mastrangelo, S.; Tolone, M.; Di Gerlando, R.; Fontanesi, L.; Sardina, M. T.; Portolano, B.
Abstract : In the local breeds with small population size, one of the most important problems is the increase of inbreeding coefficient ( F ). High levels of inbreeding lead to reduced genetic diversity and inbreeding depression. The availability of high-density single nucleotide polymorphism (SNP) arrays has facilitated the quantification of F by genomic markers in farm animals. Runs of homozygosity (ROH) are contiguous lengths of homozygous genotypes and represent an estimate of the degree of autozygosity at genome-wide level. The current study aims to quantify the genomic F derived from ROH ( F ROH ) in three local dairy cattle breeds. F ROH values were compared with F estimated from the genomic relationship matrix ( F GRM ), based on the difference between observed v . expected number of homozygous genotypes ( F HOM ) and the genomic homozygosity of individual i ( F MOL i ). The molecular coancestry coefficient ( f MOL ij ) between individuals i and j was also estimated. Individuals of Cinisara (71), Modicana (72) and Reggiana (168) were genotyped with the 50K v2 Illumina BeadChip. Genotypes from 96 animals of Italian Holstein cattle breed were also included in the analysis. We used a definition of ROH as tracts of homozygous genotypes that were >4 Mb. Among breeds, 3661 ROH were identified. Modicana showed the highest mean number of ROH per individual and the highest value of F ROH, whereas Reggiana showed the lowest ones. Differences among breeds existed for the ROH lengths. The individuals of Italian Holstein showed high number of short ROH segments, related to ancient consanguinity. Similar results showed the Reggiana with some extreme animals with segments covering 400 Mb and more of genome. Modicana and Cinisara showed similar results between them with the total length of ROH characterized by the presence of large segments. High correlation was found between F HOM and F ROH ranged from 0.83 in Reggiana to 0.95 in Cinisara and Modicana. The correlations among F ROH and other estimated F coefficients were generally lower ranged from 0.45 ( F MOL i − F ROH ) in Cinisara to 0.17 ( F GRM − F ROH ) in Modicana. On the basis of our results, recent inbreeding was observed in local breeds, considering that 16 Mb segments are expected to present inbreeding up to three generations ago. Our results showed the necessity of implementing conservation programs to control the rise of inbreeding and coancestry in the three Italian local dairy cattle breeds.